Ibika’s House of Love and Suffering (A Look into the Story Ibikina kuća by Aleksandar Tišma) - Radosavljević, Anica M. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The paper deals with the analysis of Ibikina kuća, the first published story by Aleksandar Tišma and one of his most important works. The aim of the paper is to shed light on the author’s idea of ‘a house of love’ whose fate was affected by World War II. Aleksandar Tišma often dealt with the issues of prostitution and brothels in his work. The analysis will provide an insight into the effects of the war on the existential change in the structure of the brothel and on its owner. Furthermore, the parallel between the fate of the brothel and that of Ibika—from their rise to their degradation—will be emphasized.
Keywords: Tišma; prostitution; war; eros; degradation